The radiation-induced chemistry in solid xenon matrices - Feldman, V.I.; Kobzarenko, A.V.; Orlov, A.Y.; Sukhov, F.F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The paper presents an overview of recent studies on the radiation-chemical transformations of guest molecules in solid xenon induced by fast electrons and x-ray irradiation. Specific features of the experimental approach based on combination of matrix isolation IR and EPR spectroscopy are briefly outlined (with particular impact on using monoisotopic and isotopically enriched xenon matrices). The results reveal rich and diverse radiation-induced chemistry in solid xenon, which is considered in the following major aspects: (1) matrix-induced and matrix assisted transformations of the primary guest radical cations; (2) production and dynamics of hydrogen atoms; (3) formation of xenon hydrides. Finally, preliminary results on the radiation-induced generation of oxygen atoms and ions in solid xenon are presented.